PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA ELEMEN DASAR-DASAR FOTOGRAFI KELAS X DKV DI SMK NEGERI 1 PASAMAN - Luthfiyah Ummi Kulsum; Ami Anggraini Samudra; Rahayu Trisetyowati Untari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a web-based learning media for the subject of Basic Visual Communication Design (VCD), focusing on the basic elements of photography for Grade X students of the Visual Communication Design program at SMK Negeri 1 Pasaman. The study was motivated by the limited use of interactive digital learning media, as the learning process was still dominated by printed textbooks and PowerPoint presentations, which resulted in low student engagement and suboptimal learning outcomes. This research employed a Research and Development (R&D) method using an iterative Software Development Life Cycle (SDLC) model, consisting of requirement analysis, design and development, testing, and implementation stages. The developed product is a web-based learning media equipped with interactive learning materials, quizzes, tutorial videos, 3D camera objects, a student work gallery, and discussion forums. The research subjects included media experts, subject matter experts, teachers, and Grade X VCD students. Data were collected through validation and practicality questionnaires and analyzed using descriptive quantitative techniques. The results indicate that the developed learning media achieved a very high level of validity, with scores of 96.18% from media experts and 98.43% from subject matter experts. In addition, the practicality assessment showed very high results, with scores of 98.12% from teachers and 96.03% from students. Therefore, the web-based learning media is considered valid and practical for use in photography learning and can enhance learning interactivity, facilitate independent learning, and support teachers in delivering instructional content more effectively.